2022
DOI: 10.1186/s12871-022-01701-w
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume is useful for predicting weaning failure: a retrospective, observational study

Abstract: Background To evaluate the usefulness of mean platelet volume (MPV), a marker of inflammation and stress, for predicting weaning failure in patients undergoing invasive mechanical ventilation (IMV) compared to traditional inflammation markers. Methods The retrospective observational study including patients who received IMV and underwent spontaneous breathing trial (SBT) was conducted in ICU at Beijing Chao-Yang hospital in China from January, 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…It has been reported that there were 14.5% of postoperative patients among the patients receiving mechanical ventilation in intensive care unit(ICU) [ 3 ]. Although postsurgical patients tended to have lower weaning failure rate compared to medical patients in our previous study [ 4 ], those patients still face much challenge during weaning process. There are multiple mechanisms of weaning failure [ 5 7 ].…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…It has been reported that there were 14.5% of postoperative patients among the patients receiving mechanical ventilation in intensive care unit(ICU) [ 3 ]. Although postsurgical patients tended to have lower weaning failure rate compared to medical patients in our previous study [ 4 ], those patients still face much challenge during weaning process. There are multiple mechanisms of weaning failure [ 5 7 ].…”
Section: Introductionmentioning
confidence: 85%
“…All postsurgical patients intubated and mechanically ventilated for not less than 12 h were considered eligible for the study if they fulfilled the following [ 4 , 23 ]: resolution of the underlying causes of acute respiratory failure; adequate cough reflex; absence of excessive tracheobronchial secretion; adequate oxygenation (e.g., arterial oxygen saturation > 90% or arterial oxygen tension/fraction of inspired oxygen [PaO 2 /FiO 2 ] ≥ 150 mmHg, both on the FiO 2 of ≤ 0.4 and the positive end-expiratory pressure of ≤ 8 cmH 2 O); adequate ventilatory status (e.g., respiratory rate [RR] ≤ 35 breaths/min with tidal volume ≥ 5 mL/kg of predicted body weight and no significant respiratory acidosis); stable hemodynamics (e.g., heart rate [HR] < 120 beats/min; systolic blood pressure [SBP], 90–160 mmHg; and no or minimal vasopressor use); adequate mentation (e.g., arousable or glasgow coma scale ≥ 13 with no continuous sedative infusions); body temperature < 38 ℃; hemoglobinemia ≥ 80 g/L; and acceptable electrolytes. The postsurgical patients included patients admitted to the ICU immediately after surgery and patients transferred to ICU within 1 week after surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This retrospective, observational, single center study included patients receiving IMV not less than 24 h admitted to the ICU of Beijing Chao-Yang Hospital from January, 2014 to January, 2019. The following patients were excluded: Age < 18 years; pregnancy; tracheotomy or other upper airway disorders; mechanically ventilated less than 24 h; neuromuscular disease; decision to abandon or limit active treatment; incomplete data [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Complete blood cell counts were measured by an automatic blood analyzer. CRP concentrations were measured using immunoscatter turbidimetry by Goldsite Aristo (Goldsite, Ltd., China), and the normal value of CRP ranges from 0 to 5 mg/L [ 23 ]. Acute kidney injury(AKI), defined according to established criteria [ 24 ]; septic shock, defined according to established criteria [ 25 ].…”
Section: Methodsmentioning
confidence: 99%